Effects of Work Experience, Education Level, and Wages on Employee Performance with Religiosity as Moderating Variables - Iksyaniyah, Nuril; Hakim, Luqman; Listyadi, Agung (Technium Social Sciences Journal, 2021)
The study aims to determine the influence of work experience, level of education, and wages on the performance of employees with religiosity as a moderating variable. The research site was conducted at PT Cahaya Wira Sejahtera with 95 respondents. This research includes quantitative research using the Partial Least Square (PLS) method. The results of this study are variable work experience and wages have a significant influence on employee performance. While the level of education does not affect religiosity as well as employee performance. Work experience affects religiosity and wages have no effect on religiosity. Religiosity affects employees ' performance and is capable of the dissemination of the relationship between work experience and employee performance. However, Religiosity is not able to process the relationship level of education and wages to employee performance. This is in line with the research results explaining that the level of education has no effect on employee performance because the workload provided does not require high education. Then the reverse result is in the wage variable where the wage variable affects the employee's performance but if mediated with religiosity has no effect on the employee's performance. This can be caused by the level of religiosity of employees of PT. Cahaya Wira Sejahtera, which is likely less so high that it has not been able to process the effect of wages on employee performance.